2018
DOI: 10.1094/mpmi-11-17-0262-r
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of a Unique Integrated Domain Nucleotide-Binding Leucine-Rich Repeat Gene in Wheat Abolishes Diuraphis noxia Resistance

Abstract: Plants respond in a similar manner to aphid feeding as to pathogen attack. Diuraphis noxia is a specialist aphid, feeding only on selected grasses that include wheat, barley, and oats. The wheat-Diuraphis noxia interaction is characterized by responses very similar to those seen in wheat-pathogen interactions with none of the underlying resistance pathways and genes characterized yet. From wheat harboring the Dn1 resistance gene, we have identified a nucleotide-binding leucine-rich repeat (NLR) gene containing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Knockdown of TaAGO5 showed that an efficiency of 43 and 22% was reached for Tugela and Tugela DN, respectively ( Figure 2B). The knockdown level for Tugela was similar to previous gene reports for this interaction (Nicolis and Venter, 2018), but the Tugela DN levels were knocked down to higher remaining levels. The selected control plants to test the effect of the empty vector in the experiment, resulted in fivefold higher levels of TaAGO5 being induced.…”
Section: Role Of Argonaute 5 In the Wheat-d Noxia Interactionsupporting
confidence: 86%
See 2 more Smart Citations
“…Knockdown of TaAGO5 showed that an efficiency of 43 and 22% was reached for Tugela and Tugela DN, respectively ( Figure 2B). The knockdown level for Tugela was similar to previous gene reports for this interaction (Nicolis and Venter, 2018), but the Tugela DN levels were knocked down to higher remaining levels. The selected control plants to test the effect of the empty vector in the experiment, resulted in fivefold higher levels of TaAGO5 being induced.…”
Section: Role Of Argonaute 5 In the Wheat-d Noxia Interactionsupporting
confidence: 86%
“…This level of prolonged and intensive feeding results in leaf rolling and the formation of chlorotic lesions that extend to chlorotic streaking in highly susceptible plants (du Toit and Aalsberg, 1980). Although not isolated yet, it is hypothesized that extensive effector secretion induces the different phenotypic effects when feeding (Nicolis and Venter, 2018). The aphid is unique in that it changes the turgor pressure in leaf cells to allow the leaves to roll up.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to recognition of plant pathogens, so far only a handful of resistance ( R ) genes have been identified against insect herbivores, encoding cell surface receptors (pattern recognition receptors, PRRs) and intracellular receptors (nucleotide‐binding leucin rich‐repeat, NLRs) (Kourelis & van der Hoorn, 2018; Snoeck et al, 2022). Known resistance traits against insects based on R genes are mainly limited to sap‐sucking insects, including gall midges (Bentur et al, 2016), aphids (Botha et al, 2005; Dogimont et al, 2014; Klingler et al, 2009; Nicolis & Venter, 2018; Rossi et al, 1998; Sun et al, 2020), whiteflies (Nombela, Williamson, & Muñiz, 2003) and planthoppers (Liu et al, 2015; Tamura et al, 2014; Zhao et al, 2016). Reports on R ‐genes mediating resistance to leaf‐chewing insects are even more scarce, with few reports on PRRs associated with defence against caterpillars (Gilardoni et al, 2011; Hu et al, 2018; Steinbrenner et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, only a handful of R genes, of both PRRs and NLRs type, are effective against insect herbivores, mainly limited to piercing-sucking insects such as gall midges (Harris et al2012;Bentur et al2016), aphids (Rossi et al1998;Botha et al2005;Klingler et al2009;Dogimont et al2014;Nicolis and Venter, 2018;Sun et al2020), whiteflies (Nombela et al2003), and planthoppers (Tamura et al2014;Liu et al2015;Zhao et al2016). While defense to chewing caterpillars is polygenic, a few reports suggest that PRR surface receptors also mediate these defenses (Gilardoni et al 2011, Hu et al 2018, Steinbrenner et al 2021.…”
Section: Introductionmentioning
confidence: 99%